Two new species of Oxycera and description of the female of O. signata Brunetti from China (Diptera, Stratiomyidae) - Yang, Zaihua; Wei, Lianmeng; Yang, Maofa (Zootaxa, 2009)
Two new species, Oxycera qiana sp. nov. and Oxycera micronigra sp. nov., are described from China. Oxycera signata Brunetti, 1920 is recorded for the first time from China with the female described for the first time. Diagnostic characters of all three species are illustrated. A key to the Chinese Oxycera species (19 spp.) is presented.